Methylone, a rapid acting entactogen with robust anxiolytic and antidepressant-like activity - Warner-Schmidt, Jennifer; Pittenger, Christopher; Stogniew, Martin; Mandell, Blake; Olmstead, Sarah J.; Kelmendi, Benjamin (Frontiers in Psychiatry, 2023)
Selective serotonin reuptake inhibitor (SSRI) antidepressants represent first-line pharmacological treatment for a variety of neuropsychiatric illnesses, including major depressive disorder (MDD), anxiety, and post-traumatic stress disorder (PTSD), which show high rates of comorbidity. SSRIs have a delayed onset of action. Most patients do not show significant effects until 4-8 weeks of continuous treatment, have impairing side effects and as many as 40% of patients do not respond. Methylone (3,4-methylenedioxy-N-methylcathinone; MDMC, k-MDMA, M1) is a rapid-acting entactogen that showed significant benefit in a clinical case series of PTSD patients and was well-tolerated in two Phase 1 studies of healthy volunteers. Based on these early observations in humans, in the current study we tested the hypothesis that methylone has antidepressant-like and anxiolytic effects in preclinical tests. For all studies, 6–8-week-old male Sprague Dawley rats (N=6-16) were used. We employed the Forced Swim Test (FST), a classic and widely used screen for antidepressants, to explore the effects of methylone and to probe dose-response relationships, durability of effect, and potential interactions with combined SSRI treatment. We compared the effect of methylone with the prototypical SSRI fluoxetine. Three doses of fluoxetine (10 mg/kg) given within 24h before FST testing caused a 50% reduction in immobility compared with controls that lasted less than 24h. In contrast, a single dose of methylone (5-30 mg/kg) administered 30 min prior to testing produced a rapid, robust, and durable antidepressant-like response in the FST, greater in magnitude than fluoxetine. Immobility was reduced by nearly 95% versus controls and effects persisted for at least 72h after a single dose (15 mg/kg). Effects on swimming and climbing behavior in the FST, which reflect serotonergic and noradrenergic activity, respectively, were consistent with studies showing that methylone is less serotoninergic than MDMA. Fluoxetine pretreatment did not change methylone’s antidepressant-like effect in the FST, suggesting the possibility that the two may be co-administered. In addition, methylone (5-30 mg/kg) exhibited anxiolytic effects measured as increased time spent in the center of an open field. Taken together, and consistent with initial clinical findings, our study suggests that methylone may have potential for treating depression and anxiety.